2016
DOI: 10.1111/jfpp.12719
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Physical Properties of Pea Starch Edible Films in the Presence of Glycerol

Abstract: The mechanical properties and moisture sorption at relative humidity (RH) range of 11–94%, water vapor permeability (WVP), solubility in water and color of the pea starch films as a function of glycerol were examined. The results showed that increasing the concentration of plasticizer resulted in improvement of the tensile strength of the films at RH <43%, the percent elongation as well as the deformation at break at RH <84%. Increasing plasticizer content and RH also resulted in films with lower Young's modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 94 publications
(193 reference statements)
2
61
0
Order By: Relevance
“…This behavior could be owing to their hydrophilicity nature and accessible hydroxyl groups which are capable to interact with water by hydrogen bonds. Thus, water molecules are more freely absorbed into the surface of the films (i.e., higher solubility) and permeate through the film structure more simply (i.e., higher diffusivity) bringing about the increase in WVP . The addition of glycerol can make the film less compact by increasing the molecular mobility and enhancing free volume in the film network and can increase the sorption of water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This behavior could be owing to their hydrophilicity nature and accessible hydroxyl groups which are capable to interact with water by hydrogen bonds. Thus, water molecules are more freely absorbed into the surface of the films (i.e., higher solubility) and permeate through the film structure more simply (i.e., higher diffusivity) bringing about the increase in WVP . The addition of glycerol can make the film less compact by increasing the molecular mobility and enhancing free volume in the film network and can increase the sorption of water.…”
Section: Resultsmentioning
confidence: 99%
“…After the permeation tests, the film thickness was measured and WVP (g Pa −1 s −1 m −1 ) was calculated as: WVP=ΔmAΔtXΔP where Δ m /Δ t is the weight of moisture gain per unit of time (g/s), X is the average film thickness (mm), A is the area of the exposed film surface (m 2 ), and Δ P is the water vapor pressure difference between the two sides of the film (Pa). WVP was measured for three replicated samples for each type of film .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, it has been demonstrated that pea starch in combination with guar gum produced biocomposite edible films with desirable physical, optical, and mechanical characteristics . It was shown that pea starch and guar gum (PSGG) can be potential alternatives for production of renewable source‐based biodegradable edible coatings owing to their long polymeric chain, high molecular weight, and wide availability.…”
Section: Introductionmentioning
confidence: 99%